Analisis Yuridis Legalitas Cryptocurrency dalam Perspektif Hukum Ekonomi Syariah - Errangga Januardi Santana; Muhammad Yardan Firjatulloh; Alif Ramadhani Rusmaneka; Baidhowi Baidhowi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of cryptocurrency as part of financial technology innovation has created new dynamics in the legal system, particularly regarding its legality from the perspective of positive law and Islamic economic law. This study aims to analyze the legal status of cryptocurrency in Indonesia and assess its compliance with Sharia principles, namely usury (riba), gharar (gharar), maysir (consequential risk), and maqashid (consequential risk). The research method used is normative legal research with a qualitative approach through literature review. The results indicate that under Indonesian positive law, cryptocurrency is not recognized as legal tender, but is recognized as a commodity that can be traded on a futures exchange. Meanwhile, from the perspective of Islamic economic law, the legality of cryptocurrency is conditional, depending on the mechanism of use and its level of compliance with Sharia principles. Cryptocurrency does not involve usury in direct buying and selling transactions, but it has the potential to involve gharar and maysir due to price volatility and speculative practices. The maqashid (consequential risk) approach of Sharia demonstrates that cryptocurrency has potential benefits, but also carries risks that need to be managed. Thus, an integration of positive law and Sharia principles is necessary to create regulations that are adaptive, fair, and provide legal certainty for the public